A new fuzzy MCDM model to select wireless network types in healthcare facilities - Mohammed Al-Hubaishi,; Salaheddine Bendak,; Musab A. M. Ali, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In recent years, there has been a noticeable rise in the need for wireless network connection in healthcare facilities. This is a result of the requirement for immediate access to patient data as well as the growing number of medical devices that are internet-connected. To guarantee dependable and secure communication as well as support for diverse healthcare applications and services, it is essential to choose the right wireless network type. However, the selection procedure can be difficult because it includes a number of variables that are frequently arbitrary and subjective. The difficulties of choosing the best wireless network type to be used in healthcare facilities are addressed in this research by the introduction of a new fuzzy model for multi-criteria decision-making (MCDM). The approach considers several evaluation factors, including patient cost, patient privacy, patient safety, and patient comfort and convenience. The model uses a fuzzy analytic hierarchy process (FAHP) to compute the weights of these criteria. In addition, the model uses fuzzy methods like fuzzy ARAS, fuzzy EDAS, and fuzzy TOPSIS to rank the different kinds of wireless networks according to their performance. It is clear from the results that the suggested model can effectively and dependably assess different alternatives. Additionally, it provides useful and practical advice on how to choose the right wireless network types for medical facilities. The best feature is that this approach is easily adaptable to other healthcare industry decision-making procedures.